Facility managers' experiences of mentorship in a district of Gauteng province, South Africa - Itumeleng G. Msiza; Thanyani G. Lumadi (AOSIS, 2024)
Background: Mentoring is recommended as a method to assist nurses in developing their leadership roles. Support and mentorship of nursing managers can yield positive results for their organisations because of the leadership quality. The lack of mentorship programmes for newly appointed facility managers has an impact on the management of the facilities. Aim: This study aims to explore and describe how facility managers experience mentorship at primary health care (PHC) facilities. Setting: Participants were drawn from 11 different PHC facilities falling under the three sub-districts: Emfuleni, mid-Vaal and Lesedi. Methods: A qualitative exploratory and descriptive research design was employed to achieve the study objectives. A non-probability purposive sampling method was used to select the facility managers from three sub-districts; a signed informed consent to participate in the study was obtained from each participant. A semi-structured interview guide was used to interview purposively selected facility managers. The interviews were audio recorded and subsequently transcribed verbatim. Data were analysed using the content analysis method. Rigour was ensured, and ethical principles measures were applied. Results: Four themes emerged from the results: the experiences on mentorship, views on mentorship, barriers to mentorship and mentorship improvement strategies. Conclusion: The study found that there was a lack of formal mentoring in the district, and there is a need for benchmarking and the development of a formal mentorship programme. Contribution: The results could be useful in identifying gaps, making recommendations to nursing management and future research. They could further broaden insight into the mentoring needs of facility managers.